Which alcohol control strategies do young people think are effective?. (16th January 2014) - de, Richard O.; Hart, Angie; Abraham, Charles; Memon, Anjum; Graber, Rebecca; Scanlon, Tom
Abstract Introduction and Aims The aims of this study were to examine young people's belief in the effectiveness of various alcohol control strategies and to identify demographic, attitudinal and behavioural correlates of perceived effectiveness. Design and Methods An online questionnaire hosted on a secure server was completed by 1418 men and women aged 16–21 years living in South‐East England. It assessed the perceived effectiveness of various alcohol control strategies. Key correlates included sensation seeking, impulsivity, conscientiousness, alcohol outcome expectancies, drink refusal self‐efficacy, perceived peer alcohol use and Alcohol Use Disorders Identification Test scores. Results The most effective strategies were perceived to be enforcing responsible service legislation, strictly monitoring late‐night licensed premises and teaching alcohol refusal skills. Greater belief in the effectiveness of alcohol control strategies was expressed by older participants, those who consumed less alcohol and those who expected more negative outcomes from alcohol consumption. Discussion and Conclusions The data suggest that in order to increase the perceived effectiveness of alcohol control strategies, we may need to address young people's beliefs about the negative outcomes of alcohol use. Strategies that young people believe are effective may be easier to implement, but this does not imply that unpopular but effective strategies should not be tried. [de Visser RO, Hart A, Abraham C, Memon A, Graber R, Scanlon T. Which alcohol control strategies do young people think are effective? Drug Alcohol Rev 2014;33:144–151]